2011
DOI: 10.1007/978-3-642-22935-0_12
|View full text |Cite
|
Sign up to set email alerts
|

A Primal-Dual Approximation Algorithm for Min-Sum Single-Machine Scheduling Problems

Abstract: We consider the following single-machine scheduling problem, which is often denoted 1|| f j : we are given n jobs to be scheduled on a single machine, where each job j has an integral processing time p j , and there is a nondecreasing, nonnegative cost function f j (C j ) that specifies the cost of finishing j at time C j ; the objective is to minimize n j=1 f j (C j ). Bansal & Pruhs recently gave the first constant approximation algorithm with a performance guarantee of 16. We improve on this result by givin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 20 publications
0
61
0
Order By: Relevance
“…This was also our original approach to this problem, but our rounding techniques led us to the geometric approach (which is cleaner to present as several geometric results can be used as a black-box). The same LP was used in the recent works on the special case of identical release dates [19,21,26]. We conjecture that this LP has O(1) integrality gap even for general release times.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…This was also our original approach to this problem, but our rounding techniques led us to the geometric approach (which is cleaner to present as several geometric results can be used as a black-box). The same LP was used in the recent works on the special case of identical release dates [19,21,26]. We conjecture that this LP has O(1) integrality gap even for general release times.…”
Section: Resultsmentioning
confidence: 81%
“…Cheung and Shmoys [19] proposed a primal dual algorithm for GSP with identical release times. Mestre and Verschae [26] reformulated this algorithm as a local ratio algorithm and showed that it yielded a 4-approximation.…”
Section: Techniquesmentioning
confidence: 99%
“…In the special case of uniform release dates, their method achieves the constant factor of 16. Cheung and Shmoys [2011] have claimed to achieve a (2 + ε)-approximation via a primal-dual approach. However, Mestre and Verschae [2014] have recently given instances where the algorithm constructs a dual solution whose value differs from the optimal integral solution cost by a factor of 4, contradicting the claimed factor of 2 + ε.…”
Section: Relatedmentioning
confidence: 99%
“…Moreover, the cost function can be interpreted as nonuniform processor speed. Due to their universality, problems addressing generalized min-sum objectives have recently attracted much attention (see, e.g., Pruhs [2010a, 2010b], Cheung and Shmoys [2011], Epstein et al [2012], Im et al [2012], Megow and Verschae [2013], and Stiller and Wiese [2010]). …”
Section: Introductionmentioning
confidence: 99%
“…The same analysis can be done for the Min-Exp 1|| w j U j problem with uncertain due dates and deterministic processing times. Hence and from [10], where a (4 + ǫ)-approximation algorithm, for any ǫ > 0, for this class of problems was provided, we get the following result (see also Theorem 1):…”
Section: Problems With Uncertain Due Datesmentioning
confidence: 77%